FACTORS CONTRIBUTING TO DENTAL DEVELOPMENT IN CHILDREN WITH CONGENITAL FACIAL DEFECTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The process of teething and bite formation is a physiological process, which is one of the important indicators of the health and physical development of a child. However, there are a number of factors that have an unfavorable effect on this process and create an opportunity for the development of the pathological process. In this regard, despite the numerous works of domestic and foreign researchers on this topic, the development of methods for early diagnosis, prognosis of the course and outcome of the pathology of teething and occlusion formation in children remains relevant and in demand.